Exploring Factors Affecting The Mother's Knowledge about Intrauterine Device (IUD) In Bastiong Karance District of Ternate City - Sahnawy Marsaoly; Nuzliaty T. Djama (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2022)
The Family Planning Program as one of the government policies in the population sector, has high implications for quantitative and qualitative health development. To make the family planning program a success, one of the methods used is the contraceptive method. The method of contraception that is considered safe and effective is the intrauterine device (IUD), but its use is still very low compared to other contraceptives. National coverage for active family planning participants is 66%, while North Maluku Province is only 52.4%, with IUD users only 7.4%, far below injectable contraceptives at 63.7%. The purpose of this study was to determine which factors from age, education, occupation and parity were more related to the mother's knowledge about IUD. Using a descriptive method with a non-probability sampling technique, which was taken by accident, for a month to find 67 samples. The results showed that most of the respondents were aged 20-35 years old, had adequate education, employed female employees and had 2-3 children parity. Of the four factors analyzed, it shows that the work factor and the number of children 2-3 people are the respondents who use the IUD the most